Tübingen hip flexion splints for developmental dysplasia of the hip in infants aged 0-6 months - You Zhou; Rong Li; Chuan Li; Ping Zhou; Yan Li; You-hao Ke; Fei Jiang; Xiao-peng Kang (BMC, 2020)
Abstract Background Developmental dysplasia of the hip (DDH) is a common disorder in infants. The present study aimed to evaluate the efficacy and safety of the Tübingen hip flexion splints in treating DDH in infants aged 0-6 months. Methods This is a retrospective study analyzing 259 hips in 195 infants with DDH of Graf type IIc or worse classifications treated between January 2015 and December 2017. Patients were followed up for at least 6 months. Avascular necrosis of the femoral head was diagnosed using plain radiographs at the last follow-up visit according to the Bucholz-Ogden classification. Successful treatment was defined as an improvement of the Graft classification to type I, or an improvement of the International Hip Dysplasia Institute classification to type I in patients aged > 6 months. Results Treatment was deemed successful in 128 patients (83.7%). Avascular necrosis occurred in 3 patients (3 hips). Univariate analysis showed that late treatment initiation, family history of DDH, Graf type IV and bilateral involvement were independent risk factors for treatment failure (p < 0.05). The receiver operating characteristic curve showed a cut-off value of 12 weeks for age at treatment initiation regarding successful treatment. Logistic regression analysis showed that gender, breech presentation, firstborn, swaddling, birth weight > 3.5 kg, oligohydramnios, foot deformity and torticollis did not affect the success rate of treatment (p > 0.05). Conclusions The Tübingen splint showed good efficacy and safety in treating DDH in infants aged 0-6 months. Family history of DDH, Graf classification of type IV, bilateral involvement and treatment initiation after 12 weeks of age are risk factors of treatment failure. Trial registration N/A